Comparison of Higher TVET Education and ‘Normal’ Academic Education: the Determinants of Electrical Engineering Students’ Performance - Jabarullah, Noor H; Hussain, Hafezali Iqbal (International Journal of Engineering and Technology, 2018)
Previous studies have argues that performance should depend on intelligence, maturity, motivation and background. The majority of studies about performance use endogenous factor as potential determinants for success rate. Students’ perception of quality of teaching and the environment linked to their approaches play a pivotal role in their learning outcomes [1]. Academic performance of students in higher educations has been an important topic for universities [2]. Discovering the possible determinants of academic success of students is vital for universities and lecturers as well as to students themselves in various areas. It could have many implications on admission policies, teaching performance and modification in teaching styles. The main aim of this study is to search for the potential determinants of performance of normal electrical engineering degree students in the compulsory / core modules and comparing with the Higher Technical and Vocational Education and Training (HTVET) approach. This study will also help to explore and link factors that are believed to influence the students’ performance factors that will help to improve overall university teaching and quality. Findings based from extrinsic factors in this research can provide some recommendations about University student admissions and budgeting policies and the different exogenous factors influencing students’ performance for different programme structure.